Significance of Crosslinking Approaches in the Development of Next Generation Hydrogels for Corneal Tissue Engineering - Promita Bhattacharjee; Mark Ahearne (MDPI AG, 2021)
Medical conditions such as trachoma, keratoconus and Fuchs endothelial dystrophy can damage the cornea, leading to visual deterioration and blindness and necessitating a cornea transplant. Due to the shortage of donor corneas, hydrogels have been investigated as potential corneal replacements. A key factor that influences the physical and biochemical properties of these hydrogels is how they are crosslinked. In this paper, an overview is provided of different crosslinking techniques and crosslinking chemical additives that have been applied to hydrogels for the purposes of corneal tissue engineering, drug delivery or corneal repair. Factors that influence the success of a crosslinker are considered that include material composition, dosage, fabrication method, immunogenicity and toxicity. Different crosslinking techniques that have been used to develop injectable hydrogels for corneal regeneration are summarized. The limitations and future prospects of crosslinking strategies for use in corneal tissue engineering are discussed. It is demonstrated that the choice of crosslinking technique has a significant influence on the biocompatibility, mechanical properties and chemical structure of hydrogels that may be suitable for corneal tissue engineering and regenerative applications.